Application of Simple Additive Weighting (SAW) Method in Selecting the Best Employee Performance (Case Study: CV. Syntax Corporation Indonesia) - Sukma Hendrian; Marsani Asfi; Rifqi Fahrudin (Jurnal Indonesia Sosial Teknologi, 2024)
This study discusses the application of the Simple Additive Weighting (SAW) method in selecting the best employee performance at CV. Syntax Corporation Indonesia. The background of the problem involves challenges in assessing and selecting the best employees objectively amidst the many assessment criteria. The purpose of the study is to implement the SAW method to improve accuracy and objectivity in performance assessment. The method used is SAW with predetermined criteria, as well as weight calculations and data normalization. The results of the study indicate that the SAW method is effective in facilitating the eval_uation process and producing more accurate employee rankings based on relevant criteria. The results of this study indicate that the SAW method can identify employees with the best performance regularly and transparently. The application of this method produces employee rankings that are consistent with the eval_uation objectives and company needs. By using SAW, CV. Syntax Corporation Indonesia is able to improve the accuracy of the assessment and provide more objective decisions in selecting the best employees. This study suggests that the SAW method be applied more widely for performance-based decision making in other companies.